Scalable Manufacture of High‐Performance Battery Electrodes Enabled by a Template‐Free Method. Issue 6 (25th April 2021) - Xiong, Ruoyu; Zhang, Yun; Wang, Yunming; Song, Lan; Li, Maoyuan; Yang, Hui; Huang, Zhigao; Li, Dequn; Zhou, Huamin
Abstract: Ion transport kinetics is identified as the major challenge of thick electrode design for high‐energy‐density lithium‐ion batteries. The introduction of vertically‐oriented structure pores, which provide fast transport pathways for Li +, can maximize the rate‐performance of electrodes while holding a high energy density. To overcome the harsh manufacturing requirements of traditional template‐based methods for the oriented‐pore electrodes, a template‐free strategy is developed to meet the large‐scale fabrication demand, in which controllable oriented microchannels are facilely constructed by vertically aggregated bubbles generated from thermal decomposition. The proposed method is demonstrated to be applicable for different active materials and compatible with industrial roll‐to‐roll manufacturing. The oriented‐pore electrodes exhibit a seven times higher capacity at 5C rate and show double the power density relative to the state of the art while maintaining a high level of energy density. The balance between the ion transport kinetics through the channels and in the matrix manifests an optimal design of the electrode structures, enabling the desired superior performance of the electrodes toward practical applications. Abstract : Scalable fabrication of high‐performance thick electrodes is implemented in this work by a template‐free approach, which is proven to be applicable to different active materials and compatible with roll‐to‐roll manufacture. The as‐fabricated oriented‐pore structure electrodes exhibit a seven times higher capacity compared to conventional structure electrodes at 5C rate and show both, a high power density and energy density.